(untitled) (Acta Scientiarum. Biological Sciences, 2021)
The present study aimed to study the reproduction of the Amazon turtle (Podocnemis expansa) through the evaluation of the reproductive parameters of adult females. This study was carried out in the Crixás-Açu River, municipality of Mundo Novo, state of Goiás, Brazil. In September, the biometrics of 20 females were evaluated during the spawning period. Their nests were marked for subsequent evaluation of hatchlings, measuring the distances of each nest to the river and vegetation. The second stage consisted of the evaluation of hatchlings and characterization of nests after egg hatching. The data were tested using the Pearson Correlation to measure the degree of linear correlation between the variables analyzed, such as the parameters of females, hatchlings, nests, and eggs. Nest depth was positively correlated with the number of eggshells found. We also found a correlation between the number of eggsshells and the distance of nests to the vegetation. Although moderate, this result indicates that as the distance to the vegetation increases, the number of eggshells found in nests decreases. The spawning site for Amazon turtle breeding is crucial to determine a higher number of eggs hatching and better development of hatchlings. However, the literature is still very scarce regarding the choice of spawning grounds and the influence that vegetation may have on the development of freshwater turtle hatchlings in Brazil.